2017
DOI: 10.1155/2017/6081374
|View full text |Cite
|
Sign up to set email alerts
|

Methanolic Extract of Dill Leaves Inhibits AGEs Formation and Shows Potential Hepatoprotective Effects in CCl4 Induced Liver Toxicity in Rat

Abstract: The research was aimed at evaluating the antiglycation, antioxidant, and hepatoprotective properties of methanolic extract of Anethum graveolens (dill). The antioxidant properties, photochemical characteristics, and antiglycation effects of dill extract were measured. Carbon tetrachloride-induced hepatotoxic rats were used to show the hepatoprotective activity of dill leaves. Different concentration of dill extract (0.032, 0.065, 0.125, 0.25, 0.5, and 1 mg/mL) showed potential antioxidant ability. The extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Total oxidant status (TOS) was measured using xylenol orange, and total antioxidant capacity (TAC) was measured using the ferric ion reducing antioxidant potential (FRAP) method. 22,30 The amount of MDA, a lipid peroxidation marker, was measured…”
Section: Antioxidant Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Total oxidant status (TOS) was measured using xylenol orange, and total antioxidant capacity (TAC) was measured using the ferric ion reducing antioxidant potential (FRAP) method. 22,30 The amount of MDA, a lipid peroxidation marker, was measured…”
Section: Antioxidant Markersmentioning
confidence: 99%
“…Journal of Nanomedicine downloaded from https://www.dovepress.com/ by 44.224.250.200 on 06-Jul-2020 For personal use only. International Journal of Nanomedicine 2019:14 submit your manuscript | www.dovepress.com Dovepress Dovepress 1922 abbasi-Oshaghi et al colorimetrically using thiobarbituric acid reactive substances (TBARS) 22,30. …”
mentioning
confidence: 99%
“…The MDA concentration, as a marker of lipid peroxidation, was measured by a spectrofluorometric method based on the reaction of thiobarbituric acid with MDA. Finally, data were expressed as nmol/mg protein (21,22).…”
Section: Determination Of Malondialdehyde Levelsmentioning
confidence: 99%
“…19 The antioxidant properties of the above phytoconstituents are because of their redox activities, which allow them to have different activity such as hydrogen donors, reducing metabolites, reactive oxygen species quenchers and metal chelation. 20 It was reported that water extract fraction of dill had significant DPPH scavenging activity. The stable free radical of DPPH value is generally used to evaluate plant antioxidant ability by working as hydrogen donors or free radical scavengers.…”
Section: Discussionmentioning
confidence: 99%